A cellular automata based highly accurate memory test hardware realizing March C−. (June 2016) - Saha, Mousumi; Dalui, Mamata; Sikdar, Biplab K
Abstract: This work reports a highly accurate test structure for high speed memories. The theoretical bases of the design are the March algorithm and cellular automata (CA) proposed by von Neumann in 1950s. Theory of 3 and 5-neighborhood CA, employed for the current application, has been developed to enhance the self-testability of memory test logic. The special class of single length cycle attractor cellular automata, introduced in this work, accepts status of each memory word and evaluates it to decide on the faults in the memory. The extension of CA neighborhood to 5 enables propagation of the effect of faults in memory or in the test logic to the error line of the test structure. This overcomes the inability of classical memory test hardware designed with the ex − or and or logic.